Computational prediction of pressure change in the vicinity of tidal stream turbines and the consequences for fish survival rate. (February 2017) - Zangiabadi, E.; Masters, I.; Williams, Alison J.; Croft, T.N.; Malki, R.; Edmunds, M.; Mason-Jones, A.; Horsfall, I.
Abstract: The presence of Tidal Stream Turbines (TST) for tidal power production, leads to changes in the local physical environment that could affect fish. While other work has considered the implications with respect to conventional hydroelectric devices (i.e. hydroelectric dams), including studies such as physical impact with the rotors and pressure variation effects, this research considers the effects of sudden changes in pressure and turbulence on the hypothetical fish with respect to TSTs. Computational fluid dynamics (CFD) is used to investigate changes to the environment, and thus study the implications for fish. Two CFD methods are employed, an embedded Blade Element representation of the rotor in a RANS CFD model, and a blade resolved geometry using a moving reference frame. A new data interpretation approach is proposed as the primary source of environmental impact data; 'rate of change of pressure' with time along a streamtrace. This work also presents results for pressure, pressure gradients, shear rates and turbulence to draw conclusions about changes to the local physical environment. The assessment of the local impact is discussed in terms of the implications to individual fish passing a single or array of TST devices.